2015
DOI: 10.1016/j.ecolmodel.2015.07.015
|View full text |Cite
|
Sign up to set email alerts
|

An agent-based model to simulate tsetse fly distribution and control techniques: A case study in Nguruman, Kenya

Abstract: Background African trypanosomiasis, also known as “sleeping sickness” in humans and “nagana” in livestock is an important vector-borne disease in Sub-Saharan Africa. Control of trypanosomiasis has focused on eliminating the vector, the tsetse fly (Glossina, spp.). Effective tsetse fly control planning requires models to predict tsetse population and distribution changes over time and space. Traditional planning models have used statistical tools to predict tsetse distributions and have been hindered by limited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…Numbers of G. pallidipes caught in traps have previously correlated inversely with Landsat shortwave infrared values-an indicator of moisture (Barsi, Lee, Kvaran, Markham, & Pedelty, 2014;Kitron et al, 1996). Normalized Difference Vegetation Index (NDVI) values above 0.39 have previously been used as an indicator of vegetation suitable for tsetse (Lin, DeVisser, & Messina, 2015;Moore & Messina, 2010), based on the observation that mortality rates decrease as NDVI increases (Rogers & Randolph, 1991). The NDVI is a measure of the density of plant matter-using the near-infrared and visible red wavelengths.…”
Section: Remotely-sensed Variablesmentioning
confidence: 99%
“…Numbers of G. pallidipes caught in traps have previously correlated inversely with Landsat shortwave infrared values-an indicator of moisture (Barsi, Lee, Kvaran, Markham, & Pedelty, 2014;Kitron et al, 1996). Normalized Difference Vegetation Index (NDVI) values above 0.39 have previously been used as an indicator of vegetation suitable for tsetse (Lin, DeVisser, & Messina, 2015;Moore & Messina, 2010), based on the observation that mortality rates decrease as NDVI increases (Rogers & Randolph, 1991). The NDVI is a measure of the density of plant matter-using the near-infrared and visible red wavelengths.…”
Section: Remotely-sensed Variablesmentioning
confidence: 99%
“…These rates provide important inputs for an increasing number of models of tsetse population dynamics (Vale & Torr, 2005;Torr & Vale, 2011;Hargrove et al, 2012;Moore et al, 2012;Ackley & Hargrove, 2017;Lord et al, 2018), using techniques varying from spreadsheet models to differential equations. Recently, there has also been a growing interest in using agent-based modelswhere the lives of individual tsetse are followed at short discrete time intervals (Alderton et al, 2013(Alderton et al, , 2016(Alderton et al, , 2018Lin et al, 2015;Grébaut et al, 2016). All of the above modelling approaches can be useful for the prediction of future changes in the distribution and abundance of tsetse, and the diseases they transmit, under various intervention protocols, and in the face of possible climatic changes.…”
Section: Introductionmentioning
confidence: 99%
“…Detailed information and data on tsetse density, movement ecology, and migration rates, for the area of interest, would be needed to correctly parameterize these models. Previous modeling studies have used spatially continuous and agent-based models to evaluate the effectiveness of different control measures for reducing or eradicating tsetse flies at different spatial scales [20,25,5658]. Other studies, statistical models of species distribution, such as logistic regression and Maxent models, have been used to optimize the deployment of insecticide-treated targets, release density of sterile tsetse males, and location of monitoring traps for a tsetse eradication campaign in Senegal [59].…”
Section: Discussionmentioning
confidence: 99%
“…Future models should investigate the contribution of risk behavior to disease persistence in different g-HAT incidence intensity settings. Previous modeling studies have shown that the presence of non-human animal reservoirs would reduce the effectiveness of both medical intervention and vector control for interrupting disease transmission in high transmission intensity foci [14,15,20,25,5658]. Therefore, tsetse migration and non-human animal reservoirs may have a synergistic impact in reducing the effectiveness of vector control measures.…”
Section: Discussionmentioning
confidence: 99%